Performance evaluation of shuttle-based storage and retrieval systems using discrete-time queueing network models - Epp,Martin (Wissenschaftliche Berichte des Instituts für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2018)
Shuttle-based storage and retrieval systems (SBS/RSs) are an important part of today's warehouses. In this work, a new approach is developed that can be applied to model different configurations of SBS/RSs. The approach is based on the modeling of SBS/RSs as discrete-time open queueing networks and yields the complete probability distributions of the performance measures.